Black humour processing in the light of the conceptual integration theory and the benign violation theory - Avdagić Kemal (ExELL (Explorations in English Language and Linguistics))
The aim of the paper is to reveal that humour processing is an exertion which requires both, mental and emotional capacities. To prove the point, two theories for humour processing were employed: the conceptual integration theory and the benign violation theory. The paper shows that theories, though different, possess certain common elements and represent useful tools in humour processing. The conceptual integration theory, with its input spaces, blending processes and generic space, together with the benign violation theory and its detection of humorous elements within tragic situations, could be valuable assets in understanding how people find humour in intimidating and life-threatening situations. The paper also sheds some light on how different age groups perceive black humour showing that age and life experience facilitate understanding of black humour.